2020
DOI: 10.1038/s41598-020-64148-4
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of gastroenteritis by emerging norovirus GII.2[P16] in a kindergarten in Kota Kinabalu, Malaysian Borneo

Abstract: outbreaks of diarrhea in kindergartens are underreported and frequently go unnoticed in developing countries. to better understand the etiology this study was performed during an outbreak of diarrhea in a kindergarten in Sabah, Malaysia. outbreak investigation was performed according to the standard procedures. In this outbreak a total of 34 (36.5%) children and 4 (30.8%) teachers suffered from gastroenteritis. Stool samples from seven children and 13 teachers were tested for rotavirus and norovirus. During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Human-to-human transmission of NoV is common, mainly by the fecal-oral route (particularly for the epidemic strain GII.4); although, spread may be enhanced by episodes of vomiting [59]. NoV can efficiently survive in the environment and resists freezing temperatures, heating to 60 • C, and disinfection with chlorine or alcohol-facilitating contamination of food, water, and inanimate surfaces [60]-eventually leading to outbreaks, especially in close settings as daycare centers, schools [46,61], hospitals, military camps, and cruise ships [41,62], among others. NoV is highly contagious due to its very low infectious dose; a single particle has an infection probability of 50%, although a doseresponse relationship has been noted, in which individuals exposed to higher numbers of viruses experience a higher infectious rate [34,47,61,63].…”
Section: Transmission and Sheddingmentioning
confidence: 99%
“…Human-to-human transmission of NoV is common, mainly by the fecal-oral route (particularly for the epidemic strain GII.4); although, spread may be enhanced by episodes of vomiting [59]. NoV can efficiently survive in the environment and resists freezing temperatures, heating to 60 • C, and disinfection with chlorine or alcohol-facilitating contamination of food, water, and inanimate surfaces [60]-eventually leading to outbreaks, especially in close settings as daycare centers, schools [46,61], hospitals, military camps, and cruise ships [41,62], among others. NoV is highly contagious due to its very low infectious dose; a single particle has an infection probability of 50%, although a doseresponse relationship has been noted, in which individuals exposed to higher numbers of viruses experience a higher infectious rate [34,47,61,63].…”
Section: Transmission and Sheddingmentioning
confidence: 99%
“…(c) The construction of a phylogenetic tree using MEGA 7.0 software. The analysis of the self-expansion was performed after 1,000 times of repeated sampling by the Neighbor-joining method 53 .…”
Section: Resultsmentioning
confidence: 99%
“…GII genogroup viruses are the most commonly detected in humans; they can be further divided into 27 confirmed genotypes and 37 P types. From the mid-1990s to 2014, GII.4 genotype and its new variants have caused about 70%−80% of all NoVassociated AGE outbreaks worldwide (3) (4)(5)(6). The occurrence of GII.2[P16] from sporadic to large-scale outbreaks suggested that the reemergence and sudden epidemic may be related to the change of viral biological properties, which led to stronger transmissive and infective ability.…”
Section: Genomic Feature and Genetic Diversity Of Novmentioning
confidence: 99%
“…GII.2[P16] recombinant NoV first appeared in Japan in 2008 and caused AGE outbreaks in Osaka at that time and then was occasionally detected in sporadic cases. In 2016, GII.2[P16] NoV reemerged in Guangdong Province, China, and rapidly became the main epidemic strain in Asian countries ( 4 - 6 ). The occurrence of GII.2[P16] from sporadic to large-scale outbreaks suggested that the reemergence and sudden epidemic may be related to the change of viral biological properties, which led to stronger transmissive and infective ability.…”
Section: Introductionmentioning
confidence: 99%